PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA LABORATORIUM PARAHITA DIAGNOSTIC CENTER BSD SERPONG TANGERANG - Mutmainnah Mutmainnah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
his study aims to determine how much the influence of service quality on customer satisfaction. And the company which is the object of this research is the BSD Serpong Parahita Diagnotic Center Laboratory. The research method used is associative descriptive with a quantitative approach. The population in this study were customers at the BSD Serpong Parahita Diagnotic Center Laboratory. By using unsaturated samples as many as 96 respondents. Data collection techniques by means of questionnaires, and data analysis techniques are validity test, reliability test, simple linear regression analysis, correlation coefficient analysis, coefficient of determination, and, hypothesis testing. There is a significant effect on customers of the BSD Serpong Parahita Diagnostic Center Laboratory. This can be seen from a simple linear regression equation that is Y = 7.680 + 0.390x, which means that Y changes run in two directions with changes in X. So each increase in the value of X will be followed by a decrease in the value of Y, and vice versa the value of X decreases. Y will increase. So it can be concluded that the influence of service quality on customer satisfaction. And from the correlation coefficient found at 0.700 so that it can be said to be very strong between the environment and employee performance at the BSD Serpong Parahita Diagnotic Center Laboratory, the environment determination coefficient has a positive effect on the performance variable of 49.1% while the remaining 50.9% is influenced by other variables which is unknown to researchers. And the value of tcount> t table, or (9.515> 1.661) means that there is a significant influence between the influence of service quality on customer satisfaction at the BSD Serpong Parahita Diagnostic Center Laboratory.